Gut microbiota and type 2 diabetes associations: a meta-analysis of 16S studies and their methodological challenges - Machado, Jésica Lígia Picanço; Schaan, Ana Paula; Mamede, Izabela; Fernandes, Gabriel Rocha (Frontiers in Microbiomes, 2025)
Diabetes mellitus is a prevalent chronic non-communicable disease, and recent studies have explored the link between gut microbiota and its development. Despite some evidence suggesting an association, the influence of gut microbiota on type 2 diabetes (T2D) remains unclear. A systematic search of PubMed (January 2016– December 2023) using the keywords “16S” and “diabetes” or “DM2” or “T2DM” or “T2D” and “gut microbiota” and “diabetes” or “DM2” or “T2DM” or “T2D”. The studies included compared gut microbiome diversity between diabetic and non-diabetic adults using 16S rRNA sequencing, excluding children, interventions, and type 1 diabetes. Alpha diversity indices and bacterial mean abundance were analyzed, with statistical assessments using a random-effects model and I2 for heterogeneity. Thirteen studies met the criteria, with the Shannon index being the most commonly used measure. Results showed significant heterogeneity (I2 > 75%) and no notable differences between diabetic and non-diabetic groups. Other indices, such as Chao1 and phylogenetic whole tree, similarly showed no consistent differences. Taxonomic analysis also failed to find phyla consistently correlated with T2D, with variability across studies. The relationship between gut microbiota and diabetes remains uncertain due to technical and biological factors that are often overlooked. The inconsistencies across studies highlight the low reproducibility common in microbiota research.